Cytokeratin-1 is essential for the detection of laminar shear stress in endothelial cells - Sunyoung Ahn; Youngsik Seo; Heonyong Park (Animal Cells and Systems)
Endothelial cells regulate diverse vascular functions by perceiving and reacting to laminar shear stress. In this study, a novel shear-sensing receptor was identified through the use of a pro-inflammatory protein, lysyl-tRNA synthetase (KARS), which is known to be secreted from endothelial cells via autophagy. Binding assays demonstrated that cytokeratin-1 (CK1) interacts with KARS at the endothelial cell surface. Additionally, CK1 was shown to be critical for ECM-cell adhesion and endothelial sensing of shear stress by mediating interactions with laminin and integrin α6. Overexpression of CK1 results in hyperactivation of endothelial nitric oxide synthase (eNOS) in response to laminar shear stress (LSS), potentially reducing the risk of atherosclerosis. Furthermore, elevated CK1 expression significantly decreases leukocyte adhesion to endothelial cells by modulating nitric oxide production stimulated by LSS. Conversely, CK1 knockdown leads to the formation of actin fibers and diminishes LSS-induced activation of several cell signaling components. These findings indicate that CK1 is a shear-sensing receptor, providing new perspectives on the close relationship between cell-to-matrix adhesion and mechanosensing.